3D characterization of nanowire devices with STEM based modes. (10th October 2019) - Bender, Hugo; Bosch, Eric G T; Richard, Olivier; Mendez, David; Favia, Paola; Lazić, Ivan
Abstract: Advanced semiconductor devices have 3D morphologies with nanometer sized features. Therefore, their structural and chemical characterization requires analysis techniques with high spatial 3D resolution. Through focal integrated differential phase contrast and high angle annular dark field scanning transmission electron microscopy (STEM) depth sectioning are among the techniques that can potentially fulfill these needs. In this work they are applied to Si and Ge nanowire structures with gate all around replacement metal gates. It is shown that with both imaging modes slicing with 2D lattice resolution through the polycrystalline gate stack and the monocrystalline wires is possible, while a resolution in the viewing direction on the order of 5 nm is obtained. Based on fast Fourier transformation analysis the crystal distribution in the gate stack and morphology of the nanowires are analyzed. Similar structures are investigated with combined STEM-energy dispersive spectroscopy 180° tomography on pillar shaped TEM specimens. Comparison of the 3D imaging modes and standard TEM/STEM imaging is discussed.